Neutron generation enhanced by a femtosecond laser irradiating on multi-channel target - Yang, Yanlei; Lv, Chong; Sun, Wei; Ban, Xiaona; Liu, Qiushi; Deng, Zhigang; Qi, Wei; Yang, Guoqing; Zhang, Xiaohua; Wan, Feng; Wang, Zhao; Zhao, Baozhen; et al. (Frontiers in Physics, 2023)
A novel scheme has been proposed to enhance neutron yields, in which a multi-channel target consisting of a row of parallel micro-wires and a plane substrate is irradiated by a relativistic femtosecond laser. Two-dimensional particle-in-cell simulations show that the multi-channel target can significantly enhance the neutron yield, which is about 4 orders of magnitude greater than the plane target. Different from the case of nanowire target, we find that when the laser penetrates into the channel, the excited transverse sheath electric field can effectively accelerate the D+ ions in the transverse direction. When these energetic D+ ions move towards the nearby wire, they will collide with the bulk D+ ions to trigger D-D fusion reaction and produce neutrons, which is much more effective than the plane target case. Due to the unique trajectory of the incident D+ ions, the angular distribution of the produced neutrons is modulated from isotropic to two peaks around ±90°. Meanwhile, this enhancement and modulation is further verified in a wide range of target parameters.